2013
DOI: 10.5194/acp-13-2757-2013
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-resolving chemistry simulation of a Hector thunderstorm

Abstract: Cloud chemistry simulations were performed for a Hector thunderstorm observed on 16 November 2005 during the SCOUT-O3/ACTIVE campaigns based in Darwin, Australia, with the primary objective of estimating the average NO production per lightning flash in this unique storm type which occurred in a tropical island environment. The 3-D WRF-Aqueous Chemistry (WRF-AqChem) model is used for these calculations and contains the WRF nonhydrostatic cloud-resolving model with online gas- and aqueous-phase chemistry and a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…11). Similar underestimation of the w max formulation has been noted for both tropical (Hector storm near Darwin, Australia) and US continental storms (Cummings et al, 2013). These results indicate that it is important to evaluate the flash rate parameterizations with observations.…”
Section: Sensitivity To Formulationsupporting
confidence: 69%
“…11). Similar underestimation of the w max formulation has been noted for both tropical (Hector storm near Darwin, Australia) and US continental storms (Cummings et al, 2013). These results indicate that it is important to evaluate the flash rate parameterizations with observations.…”
Section: Sensitivity To Formulationsupporting
confidence: 69%
“…For example, Cummings et al (2013) see an overestimation of modelled CO mixing ratios at anvil altitudes of a simulated Hector. Zhu et al (2013) concluded that the imperfect simulations of convection may lead to underestimation of the exchange of trace gases between troposphere and stratosphere.…”
Section: Tracersmentioning
confidence: 99%
“…Therefore, the factor-of-four uncertainty currently associated with the global LNO x source strength stems primarily from the uncertainty in the global mean NO x production per flash. Several methods have been used to estimate this quantity: theoretical estimates [Price et al, 1997;Koshak et al, 2014], laboratory experiments ], cloud-resolving model simulations constrained by lightning flash observations and anvil NO x measurements [DeCaria et al, 2005;Ott et al, 2007Ott et al, , 2010Cummings et al, 2013], analyses of aircraft data [Huntrieser et al, 2008[Huntrieser et al, , 2009[Huntrieser et al, , 2011, and analyses of satellite observations [Beirle et al, 2004[Beirle et al, , 2006[Beirle et al, , 2010Bucsela et al, 2010]. NO x production estimates from these studies vary from 30 to 1100 mol flash À1 , though most estimates fall between 100 and 500 mol flash…”
mentioning
confidence: 99%